Honey Bees and Colony Collapse Disorder: A Pluralistic Reframing. Issue 5 (6th May 2016) - Watson, Kelly; Stallins, J. Anthony
Abstract: Scientific narratives surrounding colony collapse disorder (CCD) are often played against one another. However, oppositional knowledge politics do not neatly segregate the materiality and causal properties of the ecological phenomena they represent. Thus the challenge with CCD is not just to describe the partisan character of how knowledge about it is socially produced. It is also about how to integrate these politics through their less antagonistic material ecologies. We review three dominant discourses underlying CCD and honey bee decline and present a synthesis that conveys how their socially embedded perceptions about ecological causality are more compatible. We invoke a theoretical framework from complexity theory to demonstrate how multiple kinds of ecological causality, from the identifiable and addressable to the more emergent and unpredictable, can align under conflicting policy positions. We argue that this continuum of ecological explanations is a more conciliatory framework for responding to CCD. It provides an alternative to the antagonistic politics that tend to reify and defend either a restrictive search for a singular cause, a paralyzing documentation of all possible permutations of CCD, or a return to a utopian agrarian past. Relating how ecological knowledge is socially produced can illuminate stakeholder positions and strategies. But it is also constructive to map out how the ecological suppositions underlying them relate and inform one under.